Studi Komparatif Implementasi Gerakan CANTIK di Puskesmas Stunting Tinggi dan Rendah Kabupaten Pekalongan - Any Ayu Arrohmah; Yuniarti Yuniarti; Dewi Nugraheni Restu Mastuti; Wahyuningsih Wahyuningsih (Pelantar Press, 2026)
The implementation of the CANTIK movement in Pekalongan Regency leaves disparities between Community Health Centers (Puskesmas). Bojong 1 Community Health Center (low stunting) is able to transform the seven theoretical variables into adaptive local practices, while Siwalan Community Health Center (high stunting) still faces systemic weaknesses. This study aims to examine the seven theoretical variables. The method used is a qualitative, descriptive comparative case study approach, comparing Siwalan Community Health Center and Bojong 1 Community Health Center descriptively to enrich the findings. Data collection through observation, in-depth interviews with 12 key informants, and documentation. The results show that the implementation of CANTIK is effective in Bojong 1 Community Health Center because the standards and goals/targets are clearly understood, communication is structured and adaptive, cadres are trained, budget is available, task division is clear, there is no double job, commitment and strong internal support, structured administrative procedures, flexible and adaptive bureaucracy, as well as responsive political support and low myth resistance. On the other hand, the Siwalan Community Health Center faces serious obstacles such as cadres not understanding the movement, inconsistent targets, SOPs not anticipating referral rejections, communication constraints, lack of sustainability of sector collaboration, Villages not allocating Village Funds (ADD), uneven availability/quality of resources (anthropometric tools, educational media), demotivation due to rewards not commensurate with work, late reporting, low participation and strong traditions/myths. In conclusion, the success of the program is determined by the ability to transform central policies into adaptive local practices. Therefore, it is necessary to map the capacity of cadres in Siwalan, Village advocacy regarding Village Fund allocation for interventions, cadre incentives, and equipment maintenance, provide simple daily record templates, cultural approaches/key figures, while in Bojong 1 document best practices